Traditional Chinese medicine's challenge to clinical science and health policy - Justin Thomas Maher (Wolters Kluwer Health/LWW, 2018)
Traditional Chinese medicine (TCM) has been improving human health for millennia. And for that, it has gradually gained the attention of the global scientific community. TCM clinical research progresses, but slowly. I see it as being held back by perverse incentive structures in science and regulatory politics.